Motivation, Self-Concept and Discipline in Young Adolescents Who Practice Rhythmic Gymnastics. An Intervention - Gabriel González-Valero; Félix Zurita-Ortega; José Luis Ubago-Jiménez; Pilar Puertas-Molero (MDPI AG, 2020)
This study aims to develop an intervention based on TARGET strategies in young people practicing rhythmic gymnastics, with the aim of observing whether motivation, discipline, self-concept and flexibility are improved. This research is a longitudinal study of a quasi-experimental nature. A total of 104 young adolescents between the ages of 11 and 12 years (11.66 ± 0.47) participated in the study, of which 60 belong to the control group and 44 to the experimental group. The intervention programme lasted two months (17 sessions). TARGET strategies were applied to the experimental group during training. While the experimental group continued with its routine training. To measure the psychological variables, the instrument used were the Youth Physical Self-Concept Scale (C-PSQ), Reason Scale for Discipline (RSD) and Success Perception Questionnaire (SPQ), and for flexibility, the tests were applied to the Sit and Reach and Deep trunk flexion test. The results showed that those teenagers who participated in the intervention, obtained an increased climate task, which entails an enjoyment by the practice of physical activity itself, more optimal levels of physical self-concept and discipline, subsequently, obtaining better results of flexibility. While in the control group gymnasts the ego climate and demotivation increased. TARGET strategies applied to young adolescents have positive effects, improve motivation towards physical activity, self-concept and discipline. This results in greater performance in flexibility. This will encourage young adolescents to continue to engage in physical activity in the future.